Photography's Orientalism : new essays on colonial representation - Behdad, Ali, 1961-; Gartlan, Luke (Issues & debates., 2013)
The Middle East played a critical role in the development of photography as a new technology and an art form. Likewise, photography was instrumental in cultivating and maintaining Europe's distinctively Orientalist vision of the Middle East. As new advances enhanced the versatility of the medium, nineteenth-century photographers were able to mass-produce images to incite and satisfy the demands of the region's burgeoning tourist industry and the appetites of armchair travelers in Europe. In this way, the evolution of modern photography fueled an interest in visual contact with the rest of the world. Photography's Orientalism offers the first in-depth cultural study of the works of European and nonEuropean photographers active in the Middle East and India, focusing on the relationship between photographic, literary, and historical representations of this region and beyond.